An accurate self-commissioning technique for matrix converters applied to sensorless control of synchronous reluctance motor drives - Stella, Fausto; Yousefi-Talouki, Arzhang; Odhano, Shafiq; Pellegrino, Gianmario; Zanchetta, Pericle (IEEE, 2018)
The compensation of converters’ nonlinear voltage error is crucial in encoder-less control of ac motor drives. In this paper, a new self-commissioning and compensation method is proposed for matrix converters (MC). Similar to what done in the past for voltage source inverters, the MC voltage error is identified before the drive start and stored in a look-up table (LUT), later used for error compensation and accurate voltage estimate. Different from what observed in the past, the effect of parasitic capacitors on nonlinear voltage error of MCs in four-step current based commutation is observed and studied. Eventually, this method is applied to the sensorless control of a synchronous reluctance (SyR) motor drive, using the direct flux vector control (DFVC) concept. Experimental results are presented to validate the effectiveness of proposed self-commissioning in improving the performance of sensorless control at standstill and low speed.